A. 2(6a-3) = (6a-3)*2
The answer should be A because commutative prop of multiplication says you can multiply the numbers in any order and whether you put the 2 in front or behind the parenthesis doesn't affect the end result.
2(6a − 3) = (6a − 3)2 satisfy the Commutative Property of multiplication .
Definition of Commutative Property of Multiplication
Let us assume that x and y be any numbers .
x × y = y × x
This is called the Commutative Property of multiplication .
x = 2
y = 6a − 3
Put in the above property
2 × (6a -3) = (6a - 3)× 2
2(6a − 3) = (6a − 3) 2
Therefore 2(6a − 3) = (6a − 3)2 satisfy the Commutative Property of multiplication .
The Commutative Property of Multiplication states that it doesn't matter in what order you multiply terms to get the same
In this case
A: commutative property
B: distributive property
C: distributive property
D: associative property
Thus the answer is option A
The first 2(6a − 3) = (6a − 3) ⋅ 2 is an example where 2 and (6a-3) are the factors that can be swapped, because multiplication is commutative.
Answer is A: 2(6a-3) = (6a-3)2
Hope this helps :)
which of the following demonstrates the commutative property of mul...